Detection and localization of continuous gravitational waves with pulsar timing arrays: the role of pulsar terms. Issue 2 (16th June 2016) - Zhu, X.-J.; Wen, L.; Xiong, J.; Xu, Y.; Wang, Y.; Mohanty, S. D.; Hobbs, G.; Manchester, R. N.
Abstract: A pulsar timing array is a Galactic-scale detector of nanohertz gravitational waves (GWs). Its target signals contain two components: the 'Earth term' and the 'pulsar term' corresponding to GWs incident on the Earth and pulsar, respectively. In this work we present a Frequentist method for the detection and localization of continuous waves that takes into account the pulsar term and is significantly faster than existing methods. We investigate the role of pulsar terms by comparing a full-signal search with an Earth-term-only search for non-evolving black hole binaries. By applying the method to synthetic data sets, we find that (i) a full-signal search can slightly improve the detection probability (by about five per cent); (ii) sky localization is biased if only Earth terms are searched for and the inclusion of pulsar terms is critical to remove such a bias; (iii) in the case of strong detections (with signal-to-noise ratio ≳30), it may be possible to improve pulsar distance estimation through GW measurements.